0118 Increased Circulating Levels and Peripheral Tissue Promoter DNA Methylation of the Hormone FGF-21 Following Acute Sleep Loss in Humans. (12th April 2019) - Espes, Daniel; Carlson, Per-Ola; Benedict, Christian; Cedernaes, Jonathan
Abstract: Introduction: Sleep loss and circadian misalignment alter energy metabolism in a tissue-specific manner. FGF-21 has tissue-specific and nutrient-dependent effects on metabolic substrate utilization, e.g. increasing insulin sensitivity of adipose tissue, yet its role has not been investigated in humans exposed to acute sleep loss. Increased levels of FGF-21 are also seen in metabolic disease such as type 2 diabetes and obesity. Methods: In a randomized, 2-session, 2-condition, crossover clinical study involving 15 healthy young men, serum samples were obtained in the fasted state and after an oral glucose tolerance test (OGTT), following one night of sleep loss and following one night of sleep (8.5 hrs), for analysis of serum FGF-21 levels by ELISA. Skeletal muscle and adipose tissue biopsies were collected in the morning fasting state in both conditions for DNA methylation and qPCR analyses. Results: Even though the OGTT increased FGF-21 levels across conditions (P=0.0001), FGF-21 levels were significantly higher across timepoints after acute sleep loss compared with after sleep (p=0.022). A similar significant increase was seen in a separate cohort with cumulatively matching partial sleep loss (8.5 hrs). A sub-group analysis revealed that only participants with low but not high (P=0.031 vs P=0.41) insulin sensitivity, in response to the OGTT after sleep loss, exhibited a significant increase in serum FGF-21 levels after sleep loss compared with normal sleep. The promoter region of the FGF-21 gene exhibited increased DNA methylation after sleep loss compared with sleep (P<0.05), both in skeletal muscle and adipose tissue. Conclusion: Increased circulating levels of FGF-21 may constitute a counter-regulatory mechanism by which the body tries to counteract adverse effects of disrupted sleep and circadian rhythms. Increased FGF-21 could have effects on peripheral metabolism that are in line with those previously observed after overnight wakefulness. It remains to be determined whether the altered DNA methylation of the promoter of FGF-21 in peripheral tissues after sleep loss results in long-term shifts in peripheral release of FGF-21 across the sleep/wake cycle. Support (If Any): The Swedish Society for Medical Research, the Swedish Research Council and the following foundation: Swedish Brain, Åke Wiberg, NovoNordisk, Bissen Brainwalk.